2018
DOI: 10.1186/s12931-018-0753-8
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary inflammation-induced loss and subsequent recovery of skeletal muscle mass require functional poly-ubiquitin conjugation

Abstract: BackgroundPulmonary inflammation in response to respiratory infections can evoke muscle wasting. Increased activity of the ubiquitin (Ub)-proteasome system (UPS) and the autophagy lysosome pathway (ALP) have been implicated in inflammation-induced muscle atrophy. Since poly-Ub conjugation is required for UPS-mediated proteolysis and has been implicated in the ALP, we assessed the effect of impaired ubiquitin conjugation on muscle atrophy and recovery following pulmonary inflammation, and compared activation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 53 publications
3
14
0
Order By: Relevance
“…Moreover, the activation of inflammatory NF-κB signalling has been described in the skeletal muscle of this model [27]. These data are in line with the inflammatory profile reported in the current study, as we previously reported inflammatory cell recruitment, and increased gene-expression of pro-inflammatory cytokines and chemokines in these IT-LPS instilled lungs [33], and we now report increased levels of inflammatory gene expression in the gastrocnemius muscle of these mice.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Moreover, the activation of inflammatory NF-κB signalling has been described in the skeletal muscle of this model [27]. These data are in line with the inflammatory profile reported in the current study, as we previously reported inflammatory cell recruitment, and increased gene-expression of pro-inflammatory cytokines and chemokines in these IT-LPS instilled lungs [33], and we now report increased levels of inflammatory gene expression in the gastrocnemius muscle of these mice.…”
Section: Discussionsupporting
confidence: 93%
“…These changes were not associated with pronounced differences in skeletal muscle mitochondrial content. The currently reported changes in mitophagy-and mitochondrial biogenesis-associated signalling are associated with increased atrophysignalling that was previously described in this study by our group [33].…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations